Method for preparing battery-grade iron phosphate by recovering lithium iron phosphate battery black powder

By acid leaching and deep impurity removal treatment on lithium iron phosphate battery black powder, combined with oxidation precipitation and calcining steps, the problem of high impurity content in the existing technology is solved, and efficient iron phosphate recovery and impurity removal is achieved, satisfying the battery level standard.

CN119263239AInactive Publication Date: 2025-01-07SHANDONG MEIDUO TECH CO LTD +1

Patent Information

Application Number
CN202411513567.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium iron phosphate battery black powder recycling process lacks effective handy removal processes, resulting in the high content of impurities such as aluminum, copper, titanium, etc. in the recovered iron phosphate, which is difficult to meet the battery-grade standards.

Method used

After acid leaching treatment with lithium iron phosphate battery black powder, sulfuric acid and reducing agent are added to adjust the pH value, combined with sodium silicate and ion exchange resin to deeply remove impurities, and then the iron and phosphorus molar ratio is adjusted through iron salt and phosphorus salt. Oxidation precipitation and calcination were carried out to obtain battery-grade iron phosphate.

Benefits of technology

Effectively remove impurities such as aluminum, titanium, copper, etc., ensure the quality of the recovered iron phosphate, meet battery-grade standards, and avoid impurities being wrapped into iron phosphate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263239A_ABST
    Figure CN119263239A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing battery-grade iron phosphate by recovering lithium iron phosphate battery black powder, which comprises the following steps of: performing reduction acid leaching on the lithium iron phosphate battery black powder to obtain acid leaching liquid; adding sodium silicate into the acid leaching solution to adjust the pH value of the solution to 2.5-4, removing aluminum and titanium to obtain a primary impurity-removed solution, deeply removing aluminum and titanium from the impurity-removed solution by adopting ion exchange resin, and removing copper and filtering by adopting sulfide to obtain a copper-removed solution; supplementing iron is added into the copper removal liquid, the pH is adjusted to 3.5-6.5, ferrous phosphate reacts and is separated out, and ferrous phosphate is obtained; the method comprises the following steps: carrying out acid leaching on ferrous phosphate to obtain a leaching solution, adjusting the molar ratio of iron to phosphorus in the leaching solution, carrying out oxidation precipitation, adjusting the pH value of the solution again, aging, filtering, washing and drying to obtain iron phosphate dihydrate, and finally calcining to obtain the anhydrous iron phosphate. According to the method, a process route for producing iron phosphate by an ammonium method is used for reference, iron and phosphorus in the black powder of the lithium iron phosphate battery are recycled and converted into battery-grade iron phosphate in a ferrous phosphate form, impurities such as aluminum, titanium and copper are effectively removed, and the impurities are prevented from being entrained in the iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of iron phosphate preparation, and in particular relates to a method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries. Background Art

[0002] Lithium iron phosphate batteries have the advantages of low cost, high cycle times, and good high temperature stability, making them widely used in power batteries, energy storage and other fields. According to data, lithium iron phosphate batteries account for 58.3% of the total output in the field of automotive power batteries, and are increasing year by year. The average life of lithium iron phosphate batteries is about 5 to 8 years. Considering the increasing number of lithium iron phosphate batteries in the entire market, the comprehensive recycling and reuse of waste lithium iron phosphate batteries has become an urgent problem to be solved.

[0003] The recycling of lithium iron phosphate batteries is mainly based on wet recycling. At present, conventional processes only extract lithium elements, while iron and phosphorus, which account for about 35% to 50% of the total amount of lithium iron phosphate black powder, still exist in the form of waste slag, resulting in obvious waste of resources. There are currently some reports on the recovery of iron and phosphorus elements in lithium iron phosphate, which can be divided into two categories:

[0004] 1) After the battery powder is acid-dissolved, the filtrate is oxidized and the pH is adjusted to prepare iron phosphate;

[0005] 2) The ferrophosphorus slag obtained after selective lithium extraction is further acid-leached and precipitated to prepare ferric phosphate.

[0006] Due to the lack of sufficient impurity removal steps, the above two routes generally have high impurity contents such as aluminum, copper, and titanium, resulting in the recovered iron phosphate being difficult to meet the standards for battery-grade iron phosphate.

[0007] At present, the production of iron phosphate mainly includes processes such as ammonium method, sodium method and iron powder method, among which the ammonium method has been widely used due to its advantages such as small investment and low cost. The ammonium method is to react ferrous sulfate solution with monoammonium phosphate solution, then add phosphoric acid and sulfuric acid to adjust the pH, and add hydrogen peroxide to oxidize and then use ammonia water to increase the pH, and generate iron phosphate after filtering, washing and calcining. If the iron and phosphorus elements in lithium iron phosphate black powder are acid-leached and impurity-removed to obtain ferrous phosphate, it can replace the ferrous ions in ferrous phosphate and the phosphate radicals in monoammonium phosphate, as an important raw material for producing battery-grade iron phosphate by ammonium method. For example, in the prior art CN113381089A, after acid-leaching the waste lithium iron phosphate, ferrous sulfate is added to adjust the iron-phosphorus ratio, and ammonia water is used to adjust the pH to precipitate ferrous phosphate. However, due to the lack of impurity removal process, the impurity content in the obtained ferrous phosphate is difficult to control.

[0008] Therefore, how to effectively recover the iron and phosphorus elements in lithium iron phosphate black powder and remove impurities efficiently and reasonably to obtain qualified and stable battery-grade iron phosphate products is a major problem in the current recycling of lithium iron phosphate black powder. Summary of the invention

[0009] Purpose of the invention: The technical problem to be solved by the present invention is to provide a production method for converting the iron and phosphorus in the black powder of lithium iron phosphate battery into battery-grade iron phosphate in the form of ferrous phosphate by drawing on the process route of producing iron phosphate by the ammonium method.

[0010] Technical solution: The present invention adopts a method for recovering black powder of lithium iron phosphate battery to prepare battery-grade iron phosphate, comprising the following steps:

[0011] (1) adding sulfuric acid and a reducing agent to lithium iron phosphate battery black powder for leaching to obtain an acid leaching solution;

[0012] (2) adding sodium silicate to the acid leaching solution to adjust the solution pH to 2.5-4, removing aluminum and titanium, and obtaining a preliminary impurity-removing solution;

[0013] (3) using ion exchange resin to deeply remove aluminum and titanium from the impurity removal liquid to obtain a deeply impurity removal liquid;

[0014] (4) removing copper from the deep impurity removal liquid by using sodium thiamethoxam, and filtering to obtain a copper removal liquid;

[0015] (5) adding iron salt to the copper removal solution to adjust the iron-phosphorus molar ratio in the system to (1.3-2):1 to obtain an iron supplement solution, and adjusting the pH to 3.5-6.5 to allow ferrous phosphate to react and precipitate, and obtaining ferrous phosphate after washing;

[0016] (6) mixing ferrous phosphate and water to prepare a slurry, adjusting the pH value to 0.5-2, acid leaching, and filtering to obtain a leachate;

[0017] (7) Using iron salt and phosphorus salt to adjust the molar ratio of iron to phosphorus in the leachate to (0.90-0.98):1, adding oxides for oxidation precipitation, and adjusting the pH of the solution to 1.3-2.5 again. After aging, filtering, washing, and drying, dihydrated iron phosphate is obtained.

[0018] (8) Calcining dihydrate iron phosphate to obtain anhydrous iron phosphate.

[0019] The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate battery draws on the process route of producing iron phosphate by ammonium method, and recovers iron and phosphorus in the black powder of lithium iron phosphate battery in the form of ferrous phosphate and converts them into battery-grade iron phosphate; and in the process of adopting the method, the black powder of lithium iron phosphate battery is firstly acid-leached and a small amount of reducing agent is added, which can inhibit the formation of FePO4 precipitation in the acid leaching reaction and ensure that the iron in the solution is in the form of Fe 2+ On the other hand, it can make the preliminary impurity removal liquid enter the resin for adsorption and removal of Al 3+ 、Ti 4+ At the same time, prevent Fe2+ Oxidized to reduce iron loss during adsorption.

[0020] At the same time, based on the reduction acid leaching, sodium silicate is used to adjust the pH value of the acid leaching solution to 2.5-4. Under this pH value condition, aluminum phosphate, titanium phosphate and metatitanic acid in the acid leaching solution can be precipitated before ferrous phosphate, that is, Al 3+ 、Ti 4+ Precipitation and Fe 2+ No precipitation; and Al in the system 3+ It can also take precedence over Fe 2+ Combined with silicate ions to form aluminum silicate precipitation, further removing Al in the system 3+ , which increases Al 3+ On the basis of the above, combined with ion exchange resin for Al 3+ 、Ti 4+ The adsorption effect can achieve deep removal of impurities.

[0021] In addition, copper ions are initially removed using iron powder, and sodium ferram is deeply removed, and Al, Cu, and Ti impurity ions are deeply removed, avoiding the co-precipitation of impurities that exists when producing ferric phosphate using the ammonium method.

[0022] Furthermore, in step (1) of the preparation method of the present invention, the leaching is to mix the lithium iron phosphate battery black powder with water to prepare a slurry, add concentrated sulfuric acid and a reducing agent, mix and react at 30 to 80° C. for 0.5 to 5 hours, and then obtain an acid leaching solution by filtering.

[0023] Furthermore, in step (1) of the preparation method of the present invention, the solid-liquid ratio of lithium iron phosphate battery black powder to water is 1:(1.5-6.0), and the amount of concentrated sulfuric acid added is 0.6-2 times the molar amount of lithium iron phosphate in the black powder.

[0024] Furthermore, in step (1) of the preparation method of the present invention, the reducing agent is one or more of ascorbic acid, sodium bisulfite, ammonium bisulfite, sodium sulfite, and ammonium sulfite, and the amount of the reducing agent added is 0.05 to 1 mol / L.

[0025] Furthermore, in step (3) of the preparation method of the present invention, the ion exchange resin is an acidic cation exchange resin, the particle size of the ion exchange resin is 0.35 to 1.20 mm, and the flow rate for controlling adsorption during ion exchange is 1 to 5 BV / h.

[0026] Furthermore, in step (4) of the preparation method of the present invention, the amount of sodium thiamethoxam used is 1 to 5 times the molar amount of copper element in the deep impurity removal liquid, and the reaction time is 0.5 to 3 hours.

[0027] Furthermore, in step (6) of the preparation method of the present invention, the solid-liquid ratio of ferrous phosphate to water is 1:(1.5-6.0), and the acid leaching reaction is carried out at 30-80° C. for 0.5-5 h.

[0028] Furthermore, in step (7) of the preparation method of the present invention, the oxide comprises at least one of hydrogen peroxide, oxygen or ozone, and the amount of the oxide added is equal to the amount of Fe in the solution. 2+ The molar ratio is (0.5-2):1; the aging time is 1-5h.

[0029] Furthermore, in step (8) of the preparation method of the present invention, the calcination is carried out at 400-700° C. for 2-10 hours.

[0030] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the preparation method draws on the process route of producing iron phosphate by the ammonium method, and recovers the iron and phosphorus in the black powder of lithium iron phosphate battery in the form of ferrous phosphate and converts them into battery-grade iron phosphate, and effectively removes impurities such as aluminum, titanium, and copper, avoiding the impurities being entrained in the iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0033] It should be noted that the raw materials used in the present invention can be purchased from the market. Among them, the ion exchange resin is an acidic cation exchange resin, and the particle size of the ion exchange resin is 0.35-1.20 mm.

[0034] Example 1

[0035] The method for recovering black powder from lithium iron phosphate batteries to prepare battery-grade iron phosphate in Example 1 has the following process: Figure 1 As shown, the following steps are included:

[0036] (1) Take lithium iron phosphate battery black powder, the content of each element of which is shown in Table 1 below, add water to prepare a slurry at a solid-liquid ratio of 1:4, then slowly add 98% concentrated sulfuric acid (1.1 times the molar amount of lithium iron phosphate) and 0.1 mol / L ascorbic acid, and stir at 60° C. for 2 h; filter to obtain an acid leaching solution.

[0037] Table 1 Content of each element in the black powder of lithium iron phosphate battery of Example 1

[0038] Sample name Li Fe P Al Cu Ti Lithium iron phosphate black powder 1 / % 3.68 28.27 15.02 1.01 0.27 0.07

[0039] (2) Sodium silicate is added to the acid leaching solution in an amount such that the pH value of the solution reaches 2.8. After reacting for 1 hour, the aluminum and titanium are removed by filtration to obtain a preliminary impurity-removing solution.

[0040] (3) The preliminary impurity-removed filtrate is passed through an acidic cation exchange resin at a flow rate of 3BV / h to obtain a deeply impurity-removed liquid; after the resin is saturated with adsorption, it can be desorbed using a 4% hydrochloric acid solution at a flow rate of 1BV / h, followed by water washing at a flow rate of 2BV / h, and can be recycled and reused.

[0041] (4) Adding 1.5 times the molar amount of copper element sodium fumei to the deep impurity removal liquid to remove copper, reacting for 1 hour, filtering to obtain the copper removal liquid.

[0042] (5) FeSO4·7H2O is added to the copper removal solution until the iron-phosphorus molar ratio in the solution reaches 1.55:1, thereby obtaining an iron supplement solution.

[0043] (6) Slowly add 30% sodium carbonate solution to the iron supplement solution to adjust the solution pH to 4.5, filter and wash to obtain ferrous phosphate.

[0044] (7) Take the wet ferrous phosphate residue, add water to the slurry at a solid-liquid ratio of 1:4, and then slowly add 98% concentrated sulfuric acid until the pH reaches 1.0. Then, after stirring at 40°C for 1 hour, filter to obtain the leachate.

[0045] (8) adding monoammonium phosphate to the leachate until the molar ratio of iron to phosphorus in the solution reaches 0.97:1; then adding 27.5% hydrogen peroxide to oxidize and precipitate, adding ammonia to adjust the pH of the solution to 1.8, and aging the solution at 80°C for 1 hour, and finally filtering, washing, and drying to obtain dihydrated iron phosphate; the amount of hydrogen peroxide added is proportional to the amount of Fe in the solution. 2+ The molar ratio is 1:1.

[0046] (9) The dihydrated iron phosphate was calcined at 550° C. for 4 h to obtain anhydrous iron phosphate that meets battery grade standards. The contents of various elements in the anhydrous iron phosphate prepared in Example 1 are shown in Table 2 below.

[0047] Table 2 Content of each element in anhydrous ferric phosphate of Example 1

[0048] Sample name Fe P Al Cu Ti Anhydrous iron phosphate 1 36.41% 20.85% 55ppm 2ppm 46ppm

[0049] Example 2

[0050] The method for recovering black powder from lithium iron phosphate batteries to prepare battery-grade iron phosphate in Example 2 comprises the following steps:

[0051] (1) Take lithium iron phosphate battery black powder, the content of each element of which is shown in Table 3 below, add water to prepare a slurry at a solid-liquid ratio of 1:5, then slowly add 98% concentrated sulfuric acid and 0.5 mol / L ammonium bisulfite in an amount of 1.05 times the molar amount of lithium iron phosphate, and stir at 70° C. for 1.5 h; filter to obtain an acid leaching solution.

[0052] Table 3 Content of each element in the black powder of lithium iron phosphate battery of Example 2

[0053] Sample name Li Fe P Al Cu Ti Lithium iron phosphate black powder 1 / % 4.11 30.24 16.25 0.86 0.34 0.12

[0054] (2) Sodium silicate is added to the acid leaching solution in an amount such that the pH value of the solution reaches 3.3. After reacting for 1.5 hours, the aluminum and titanium are removed by filtration to obtain a preliminary impurity-removing solution.

[0055] (3) The preliminary impurity-removed filtrate is passed through an acidic cation exchange resin at a flow rate of 4BV / h to obtain a deeply impurity-removed liquid; after the resin is saturated with adsorption, a 4% hydrochloric acid solution can be used for desorption at a flow rate of 2BV / h, followed by water washing at a water washing flow rate of 2BV / h, and it can be recycled and reused.

[0056] (4) Add 2.5 times the molar amount of copper element sodium fumei to the deep impurity removal liquid to remove copper, react for 2 hours, and filter to obtain the copper removal liquid.

[0057] (5) FeSO4·7H2O is added to the copper removal solution until the iron-phosphorus molar ratio in the solution reaches 1.6:1, thereby obtaining an iron supplement solution.

[0058] (6) Slowly add 20% sodium carbonate solution to the iron supplement solution to adjust the solution pH to 5.0, filter and wash to obtain ferrous phosphate.

[0059] (7) Take the ferrous phosphate wet slag, add water to the slurry at a solid-liquid ratio of 1:5, and then slowly add 85% phosphoric acid until the pH reaches 0.8. Then, after stirring at 30° C. for 2 h, filter and obtain the leachate.

[0060] (8) adding monoammonium phosphate to the leachate until the molar ratio of iron to phosphorus in the solution reaches 0.98:1; then adding 27.5% hydrogen peroxide to carry out oxidation precipitation, adding ammonia water to adjust the pH of the solution to 1.8, and aging the solution at 80°C for 1 hour, and finally filtering, washing, and drying to obtain dihydrated iron phosphate; the amount of hydrogen peroxide added is proportional to the amount of Fe in the solution. 2+ The molar ratio is 0.5:1.

[0061] (9) The dihydrated iron phosphate was calcined at 600° C. for 3 h to obtain anhydrous iron phosphate that meets battery grade standards. The contents of various elements in the anhydrous iron phosphate prepared in Example 2 are shown in Table 4 below.

[0062] Table 4 Content of each element in anhydrous ferric phosphate of Example 2

[0063] Sample name Fe P Al Cu Ti Anhydrous iron phosphate 1 36.62% 20.89% 64ppm 1ppm 20ppm

[0064] Example 3

[0065] The method for recovering black powder from lithium iron phosphate batteries to prepare battery-grade iron phosphate in Example 3 comprises the following steps:

[0066] (1) Take lithium iron phosphate battery black powder, the content of each element of which is shown in Table 5 below, add water to prepare the slurry at a solid-liquid ratio of 1:3, then slowly add 98% concentrated sulfuric acid and 0.2 mol / L ammonium sulfite in an amount of 1.1 times the molar amount of lithium iron phosphate, and stir at 30° C. for 4 h; filter to obtain an acid leaching solution.

[0067] Table 5 Content of each element in the black powder of lithium iron phosphate battery of Example 3

[0068] Sample name Li Fe P Al Cu Ti Lithium iron phosphate black powder 1 / % 3.88 29.02 15.94 0.54 0.23 0.03

[0069] (2) Sodium silicate is added to the acid leaching solution in an amount such that the pH value of the solution reaches 2.6. After reacting for 0.5 h, the aluminum and titanium are removed by filtration to obtain a preliminary impurity-removing solution.

[0070] (3) The preliminary impurity-removed filtrate is passed through an acidic cation exchange resin at a flow rate of 3BV / h to obtain a deeply impurity-removed liquid; after the resin is saturated with adsorption, a 6% hydrochloric acid solution can be used for desorption at a flow rate of 2BV / h, followed by water washing at a water washing flow rate of 2BV / h, and it can be recycled and reused.

[0071] (4) Adding 1.3 times the molar amount of copper element sodium fumei to the deep impurity removal liquid to remove copper, reacting for 0.5 hours, filtering to obtain the copper removal liquid.

[0072] (5) FeSO4·7H2O is added to the copper removal solution until the iron-phosphorus molar ratio in the solution reaches 1.55:1, thereby obtaining an iron supplement solution.

[0073] (6) Slowly add 30% ammonia solution to the iron supplement solution to adjust the pH of the solution to 5.3, and filter and wash to obtain ferrous phosphate.

[0074] (7) Take the wet ferrous phosphate residue, add water to the slurry at a solid-liquid ratio of 1:3, and then slowly add 98% concentrated sulfuric acid until the pH reaches 1.2. Then, after stirring at 50° C. for 1 hour, filter to obtain the leachate.

[0075] (8) Adding monoammonium phosphate to the leachate until the molar ratio of iron to phosphorus in the solution reaches 0.95:1; then adding 27.5% hydrogen peroxide to oxidize and precipitate, adding ammonia water to adjust the pH of the solution to 1.9, and aging the solution at 80°C for 1 hour, and finally filtering, washing, and drying to obtain dihydrated iron phosphate; the amount of hydrogen peroxide added is proportional to the amount of Fe in the solution. 2+The molar ratio is 2:1.

[0076] (9) The dihydrated iron phosphate was calcined at 600° C. for 3 h to obtain anhydrous iron phosphate that meets battery grade standards. The contents of various elements in the anhydrous iron phosphate prepared in Example 3 are shown in Table 6 below.

[0077] Table 6 Content of each element in anhydrous ferric phosphate of Example 3

[0078] Sample name Fe P Al Cu Ti Anhydrous iron phosphate 1 36.18% 20.67% 23ppm 2ppm 25ppm

[0079] Comparative Example 1

[0080] The basic steps are the same as those in Example 1, except that in step (2), 20% sodium hydroxide solution is used instead of sodium silicate. The specific steps are as follows:

[0081] (1) Take lithium iron phosphate battery black powder, the content of each element of which is shown in Table 7 below, add water to prepare a slurry at a solid-liquid ratio of 1:4, then slowly add 98% concentrated sulfuric acid and 0.1 mol / L ascorbic acid in an amount of 1.1 times the molar amount of lithium iron phosphate, and stir at 60° C. for 2 h; filter to obtain an acid leaching solution.

[0082] Table 7 Content of each element in the black powder of lithium iron phosphate battery of comparative example 1

[0083] Sample name Li Fe P Al Cu Ti Lithium iron phosphate black powder 1 / % 3.68 28.27 15.02 1.01 0.27 0.07

[0084] (2) Add 20% sodium hydroxide solution to the acid leaching solution in an amount such that the pH value of the solution reaches 2.8. After reacting for 1 hour, remove aluminum and titanium by filtration to obtain a preliminary impurity-removing solution.

[0085] (3) The preliminary impurity-removing liquid is passed through an acidic cation exchange resin at a flow rate of 3BV / h to obtain a deep impurity-removing liquid; after the resin is saturated with adsorption, a 4% hydrochloric acid solution can be used for desorption at a flow rate of 1BV / h, followed by water washing at a flow rate of 2BV / h, and can be recycled and reused.

[0086] (4) Adding 1.5 times the molar amount of copper element sodium fumei to the deep impurity removal liquid to remove copper, reacting for 1 hour, filtering to obtain the copper removal liquid.

[0087] (5) FeSO4·7H2O is added to the copper removal solution until the iron-phosphorus molar ratio in the solution reaches 1.55:1, thereby obtaining an iron supplement solution.

[0088] (6) Slowly add 30% sodium carbonate solution to the iron supplement solution to adjust the solution pH to 4.5, filter and wash to obtain ferrous phosphate.

[0089] (7) Take the wet ferrous phosphate residue, add water to the slurry at a solid-liquid ratio of 1:4, and then slowly add 98% concentrated sulfuric acid until the pH reaches 1.0. Then, after stirring at 40°C for 1 hour, filter to obtain the leachate.

[0090] (8) adding monoammonium phosphate to the leachate until the molar ratio of iron to phosphorus in the solution reaches 0.97:1; then adding 27.5% hydrogen peroxide to oxidize and precipitate, adding ammonia to adjust the pH of the solution to 1.8, and aging the solution at 80°C for 1 hour, and finally filtering, washing, and drying to obtain dihydrated iron phosphate; the amount of hydrogen peroxide added is proportional to the amount of Fe in the solution. 2+ The molar ratio is 1:1.

[0091] (9) The dihydrated iron phosphate was calcined at 550° C. for 4 hours to obtain anhydrous iron phosphate that meets the battery grade standard. The content of each element in the anhydrous iron phosphate prepared in Comparative Example 1 is shown in Table 8 below.

[0092] Table 8 Content of each element in anhydrous ferric phosphate of comparative example 1

[0093] Sample name Fe P Al Cu Ti Anhydrous iron phosphate 1 36.41% 20.85% 505ppm 2ppm 56ppm

[0094] It can be seen from Table 2 and Table 8 that the preparation process of the present invention can achieve deep removal of Al and Ti, effectively avoiding the inclusion of impurities into the iron phosphate.

[0095] Example 4

[0096] The method for recovering black powder from lithium iron phosphate batteries to prepare battery-grade iron phosphate in Example 4 comprises the following steps:

[0097] (1) Take lithium iron phosphate battery black powder, the content of each element of which is shown in Table 9 below, add water to prepare the slurry at a solid-liquid ratio of 1:1.5, then slowly add 98% concentrated sulfuric acid and 0.05 mol / L sodium bisulfite in an amount of 0.6 times the molar amount of lithium iron phosphate, and stir at 30°C for 5 hours; filter to obtain an acid leaching solution.

[0098] Table 9 Content of each element in the black powder of lithium iron phosphate battery of Example 4

[0099] Sample name Li Fe P Al Cu Ti Lithium iron phosphate black powder 1 / % 3.88 29.02 15.94 0.54 0.23 0.03

[0100] (2) Sodium silicate is added to the acid leaching solution in an amount such that the pH value of the solution reaches 2.5. After reacting for 1 hour, the aluminum and titanium are removed by filtration to obtain a preliminary impurity-removing solution.

[0101] (3) The preliminary impurity-removed filtrate is passed through an acidic cation exchange resin at a flow rate of 1 BV / h to obtain a deeply impurity-removed liquid; after the resin is saturated with adsorption, a 6% hydrochloric acid solution can be used for desorption at a flow rate of 2 BV / h, followed by water washing at a water washing flow rate of 2 BV / h, and it can be recycled and reused.

[0102] (4) Adding 1 times the molar amount of copper element sodium fumei to the deep impurity removal liquid to remove copper, reacting for 3 hours, filtering to obtain the copper removal liquid.

[0103] (5) FeSO4·7H2O is added to the copper removal solution until the iron-phosphorus molar ratio in the solution reaches 1.3:1, thereby obtaining an iron supplement solution.

[0104] (6) Slowly add 25% ammonia solution to the iron supplement solution to adjust the pH of the solution to 3.5, and filter and wash to obtain ferrous phosphate.

[0105] (7) Take the wet ferrous phosphate residue, add water to the slurry at a solid-liquid ratio of 1:1.5, and then slowly add 98% concentrated sulfuric acid until the pH reaches 0.5. Then, after stirring at 30° C. for 5 hours, filter and obtain the leachate.

[0106] (8) adding monoammonium phosphate to the leachate until the molar ratio of iron to phosphorus in the solution reaches 0.9:1; then using oxygen for oxidation precipitation, adding ammonia water to adjust the solution pH to 1.3, and aging the solution at 80°C for 3 hours, and finally filtering, washing, and drying to obtain dihydrated iron phosphate; the amount of oxygen added is proportional to the amount of Fe in the solution. 2+ The molar ratio is 2:1.

[0107] (9) The dihydrated iron phosphate was calcined at 400° C. for 10 h to obtain anhydrous iron phosphate that meets battery grade standards. The contents of various elements in the anhydrous iron phosphate prepared in Example 4 are shown in Table 10 below.

[0108] Table 10 Content of each element in anhydrous ferric phosphate of Example 4

[0109] Sample name Fe P Al Cu Ti Anhydrous iron phosphate 1 36.40% 20.83% 199ppm 27ppm 98ppm

[0110] Example 5

[0111] The method for recovering black powder from lithium iron phosphate batteries to prepare battery-grade iron phosphate in Example 5 comprises the following steps:

[0112] (1) Take lithium iron phosphate battery black powder, the content of each element of which is shown in Table 11 below, add water to prepare the slurry at a solid-liquid ratio of 1:6, then slowly add 98% concentrated sulfuric acid and 0.6 mol / L sodium sulfite twice the molar amount of lithium iron phosphate, and stir at 80° C. for 0.5 h; filter to obtain an acid leaching solution.

[0113] Table 11 Content of each element in the black powder of lithium iron phosphate battery of Example 5

[0114] Sample name Li Fe P Al Cu Ti Lithium iron phosphate black powder 1 / % 3.88 29.02 15.94 0.54 0.23 0.03

[0115] (2) Sodium silicate is added to the acid leaching solution in an amount such that the pH value of the solution reaches 4. After reacting for 1 hour, the aluminum and titanium are removed by filtration to obtain a preliminary impurity-removing solution.

[0116] (3) The preliminary impurity-removed filtrate is passed through an acidic cation exchange resin at a flow rate of 5 BV / h to obtain a deeply impurity-removed liquid; after the resin is saturated with adsorption, a 6% hydrochloric acid solution can be used for desorption at a flow rate of 2 BV / h, followed by water washing at a water washing flow rate of 2 BV / h, and it can be recycled and reused.

[0117] (4) Adding 5 times the molar amount of copper element sodium fumei to the deep impurity removal liquid to remove copper, reacting for 1 hour, filtering to obtain the copper removal liquid.

[0118] (5) FeSO4·7H2O is added to the copper removal solution until the iron-phosphorus molar ratio in the solution reaches 2:1, thereby obtaining an iron supplement solution.

[0119] (6) Slowly add 25% ammonia solution to the iron supplement solution to adjust the pH of the solution to 6.5, and filter and wash to obtain ferrous phosphate.

[0120] (7) Take the wet ferrous phosphate residue, add water to the slurry at a solid-liquid ratio of 1:6, and then slowly add 98% concentrated sulfuric acid until the pH reaches 2. Then, after stirring at 80° C. for 1 hour, filter to obtain the leachate.

[0121] (8) adding monoammonium phosphate to the leachate until the molar ratio of iron to phosphorus in the solution reaches 0.94:1; then using ozone for oxidation precipitation, adding ammonia water to adjust the solution pH to 2.5, and aging the solution at 80°C for 5 hours, and finally filtering, washing, and drying to obtain dihydrated iron phosphate; the amount of ozone added is proportional to the amount of Fe in the solution. 2+ The molar ratio is 1:1.

[0122] (9) The dihydrated iron phosphate was calcined at 700° C. for 2 h to obtain anhydrous iron phosphate that meets battery grade standards. The content of each element in the anhydrous iron phosphate prepared in Example 5 is shown in Table 12 below.

[0123] Table 12 Content of each element in anhydrous ferric phosphate of Example 5

[0124] Sample name Fe P Al Cu Ti Anhydrous iron phosphate 1 36.30% 20.78% 13ppm 1ppm 9ppm

[0125] It can be seen from the above embodiments that the preparation method of the present invention draws on the process route of producing iron phosphate by the ammonium method, recovers the iron and phosphorus in the black powder of lithium iron phosphate battery in the form of ferrous phosphate and converts them into battery-grade iron phosphate, and effectively removes impurities such as aluminum, titanium, and copper, avoiding the impurities being entrained in the iron phosphate.

Claims

1. A method for preparing battery-grade iron phosphate by recycling black powder from lithium iron phosphate batteries, characterized in that: The steps include: (1) adding sulfuric acid and a reducing agent to lithium iron phosphate battery black powder for leaching to obtain an acid leaching solution; (2) adding sodium silicate to the acid leaching solution to adjust the solution pH to 2.5-4, removing aluminum and titanium, and obtaining a preliminary impurity-removing solution; (3) using ion exchange resin to deeply remove aluminum and titanium from the impurity removal liquid to obtain a deeply impurity removal liquid; (4) removing copper from the deep impurity removal liquid by using sodium thiamethoxam, and filtering to obtain a copper removal liquid; (5) adding iron salt to the copper removal solution to adjust the iron-phosphorus molar ratio in the system to (1.3-2):1 to obtain an iron supplement solution, and adjusting the pH to 3.5-6.5 to allow ferrous phosphate to react and precipitate, and obtaining ferrous phosphate after washing; (6) mixing ferrous phosphate and water to prepare a slurry, adjusting the pH value to 0.5-2, acid leaching, and filtering to obtain a leachate; (7) Using iron salt and phosphorus salt to adjust the molar ratio of iron to phosphorus in the leachate to (0.90-0.98):1, adding oxides for oxidation precipitation, and adjusting the pH of the solution to 1.3-2.5 again. After aging, filtering, washing, and drying, dihydrated iron phosphate is obtained. (8) Calcining dihydrate iron phosphate to obtain anhydrous iron phosphate.

2. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 1, characterized in that: In step (1), the leaching is to mix the lithium iron phosphate battery black powder with water to prepare a slurry, add concentrated sulfuric acid and a reducing agent, mix and react at 30 to 80° C. for 0.5 to 5 hours, and then obtain an acid leaching solution by filtering.

3. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 2, characterized in that: The solid-liquid ratio of the lithium iron phosphate battery black powder to water is 1:(1.5-6.0), and the amount of concentrated sulfuric acid added is 0.6-2 times the molar amount of lithium iron phosphate in the black powder.

4. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 2, characterized in that: The reducing agent is one or more of ascorbic acid, sodium bisulfite, ammonium bisulfite, sodium sulfite, and ammonium sulfite, and the amount of the reducing agent added is 0.05-1 mol / L.

5. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 1, characterized in that: In step (3), the ion exchange resin is an acidic cation exchange resin, the particle size of the ion exchange resin is 0.35 to 1.20 mm, and the flow rate of adsorption during ion exchange is controlled to be 1 to 5 BV / h.

6. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 1, characterized in that: In step (4), the amount of sodium thiamethoxam used is 1 to 5 times the molar amount of copper element in the deep impurity removal liquid, and the reaction time is 0.5 to 3 hours.

7. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 1, characterized in that: In step (6), the solid-liquid ratio of ferrous phosphate to water is 1:(1.5-6.0), and the acid leaching reaction is carried out at 30-80° C. for 0.5-5 h.

8. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 1, characterized in that: In step (7), the oxide includes at least one of hydrogen peroxide, oxygen or ozone, and the amount of the oxide added is equal to the amount of Fe in the solution. 2+ The molar ratio is (0.5-2):1; the aging time is 1-5h.

9. The method for preparing battery-grade iron phosphate by recycling black powder of lithium iron phosphate batteries according to claim 1, characterized in that: In step (8), the calcination is carried out at 400-700° C. for 2-10 hours.

Citation Information

Patent Citations

  • Method for removing iron, aluminum, calcium and titanium impurities from scandium-containing solution

    CN104498714A

  • Method for recovering iron phosphate from iron-phosphorus slag after lithium extraction of lithium iron phosphate battery

    CN111646447A

  • Method for preparing battery-grade manganese sulfate from manganese oxide ore

    CN114162872A

  • Method for preparing battery-grade iron phosphate from slag obtained after oxidation and lithium extraction of lithium iron phosphate positive electrode powder containing copper, aluminum and graphite

    CN115818603A

  • Method for preparing battery-grade iron phosphate by utilizing positive electrode powder of waste lithium iron phosphate battery

    CN116177510A

Cited By

  • Method for preparing iron phosphate from lithium extraction waste residues, iron phosphate and application of iron phosphate

    CN119976768A

  • A method for preparing ferric phosphate from lithium extraction waste, ferric phosphate and its applications

    CN119976768B

  • High-added-value recovery method for copper in black powder lithium-rich copper-containing pickle liquor of retired lithium iron phosphate battery

    CN121272218A